Optimization of load floor support system: Topology optimization in early phase development - Nilsson, Joel (My University, 2019)
Weight is major factor for delivering competitive and sustainable products in the automotive industry. Topology optimization is today a widely used tool in the industry to produce lighter and optimized components. However, it is most commonly used for high strength structural components and not for plastic components dealing with lower loads. The thesis has been carried out at the department Interior Trim at Volvo Cars which deals with a large number of plastic components which historically have a design driven development process. In an effort to lower weight of their components and reduce lead times in the development process they are looking towards topology optimization as a tool in early phase development. This thesis will act as an investigation of how topology optimization can be used at the department in an effort to work towards a development process driven by simulations. The thesis will study topology optimization with a trial case, looking at the load floor supports of an automobile trunk. The load floor supports, which are located underneath the load floor, distributes the weight of the load floor to the body-in-white. It is also used to cover the body-in-white and connect other components. The goal was to develop a methodology for how topology optimization could be used when optimizing the component in early phase development. Conclusions could then be drawn of how topology optimization could be implemented at the department from the trial case. The bulk of the work revolved around how to produce feasible concepts by looking at, the load cases used, choices made on system level as well as how to work with the volumes and parameters used in the optimization. Through the thesis work a methodology has been proposed for how topology optimization could be approached for components like the load floor supports. The general approach is to first complete a base optimization, minimizing for compliance with a higher volume fraction constraint than the targeted one, and a pretty coarse mesh, to see general areas in which material is least needed and can be removed to drive down computational cost and thereafter allow for a finer mesh to be used to more accurately depict a thin-walled structure more suitable for injection moulding. It is however noted that it is hard to actively restrict the thickness of the section created making structural performance and weight hard to predict. The thesis also resulted in some alternative ways of using topology optimization, such as making choices on system level and help determining optimum placements of connection points to the body-in-white. Noted in the thesis however is that components like the load floor support may not be the ideal target of topology optimization with the objective of minimizing weight and driving forth concepts because of the design surfaces. These surfaces are placed on top of the load floor support and are necessary to cover the body-in-white and connect to other components. To keep these surfaces and overall appearance limits the solutions and capabilities of topology optimization. Keywords: Topology Optimization, Structural Optimization, SIMP, Concept Development
Keywords: Fastkroppsmekanik; Solid mechanics